The Islamization of Suku Anak Dalam in Jambi and Animism Claims: From Aqidah to Fiqh al-Salah Consolidation - Alhusni, Alhusni; Kurniawan, Edi; Mulyatin, Prisma (Al-Risalah, 2021)
This paper discusses the Islamization of Suku Anak Dalam (Jambiâ€™s people of the jungle/the SAD) in Jambi as well as proves that the Islamization has moved from the realm of aqidah to the deepening of fiqh, especially fiqh al-á¹£alÄh, unlike previous researchersâ€™ accusations who generalized that animism is still attached to the the SAD who have converted to Islam. This paper applies field study principles combining qualitative and quantitative research methods by applying sociocultural anthropology theory, with a research object being the SAD residing in Pelempang Village, Muaro Jambi. This paper concludes that SADâ€™s Islamization has succeeded in removing animist teachings that are not in line with Islamic values. However, SADâ€™s understanding of fiqh al-á¹£alÄh is still relatively low. This is due to a low level of education, inability to read and write, remote geographical locations, barriers between the SAD and other residents, and the absence of teachers of fiqh al-á¹£alÄh who teach actively and consistently in the area.